2017
DOI: 10.1186/s12890-017-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of tissue re-biopsy in non-small cell lung cancers resistant to previous epidermal growth factor receptor tyrosine kinase inhibitor therapies

Abstract: BackgroundWhen epidermal growth factor receptor (EGFR) gene mutation-positive non-small cell lung cancer (NSCLC) acquires resistance to the initial tyrosine kinase inhibitor (TKI) treatment, reassessing the tumor DNA by re-biopsy is essential for further treatment selection. However, the process of TKI-sensitive tumor re-progression and whether re-biopsy is possible in all cases of acquired resistance to EGFR-TKI remain unclear.MethodsWe retrospectively analyzed data from 69 consecutive patients with EGFR gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Therefore, the performance of a rebiopsy is important in detecting T970M mutations in those patients. Ideally, rebiopsy should be performed in all such patients; however, it is feasible in only 68-82% of cases (12). It stands to reason to perform the rebiopsy from the site that will provide the higher probability of detecting the T790M mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the performance of a rebiopsy is important in detecting T970M mutations in those patients. Ideally, rebiopsy should be performed in all such patients; however, it is feasible in only 68-82% of cases (12). It stands to reason to perform the rebiopsy from the site that will provide the higher probability of detecting the T790M mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the results obtained by Gaut et al (15) who showed that T790M-positive patients on first-line treatment had a significantly longer PFS than T790M-negative patients (12.0 months vs. 9.0 months, p=0.021). In addition, T790M-positive patients have also been reported to have long post-progression survival (5,12).…”
Section: Discussionmentioning
confidence: 99%
“…Besides being performed in case of an inadequate first sample, re-biopsies can be performed to track tumor progression and clonal evolution. Since a re-biopsy does also not always provide sufficient tissue for molecular testing, liquid biopsies (LBs) might help overcome this issue [8][9][10]. LBs provide an alternative way of obtaining genetic information without the need for an invasive procedure, the low patient burden allows for more frequent biopsies to guide treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Although genetic testing of tumor tissue is the standard method for mutation profiling of NSCLC, the tumor biopsy is invasive and limited by accessibility. In deed, the feasibility of performing tissue biopsy is low in advanced NSCLC patients who are in metastatic stages (8). Consequently, databases built from tissue based testing may under-represent the mutation profiles of advanced NSCLC patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the clinical validation of whether cfDNA sequencing could serve as a non-invasive, alternative approach to tissue biopsy in a larger cohort of patients is needed. However, it has been reported that 20-50% of patients with advanced metastatic NSCLC are not fit for tumor biopsy testing (8,19), thus making a large-scale comparison between matched plasma and tissue samples a challenge, both logistically and ethically. In this study, we performed liquid biopsy on a large cohort of Vietnamese NSCLC patients to examine whether it can accurately represent the mutation profiles previously obtained by direct analysis of tumor derived DNA (7).…”
Section: Introductionmentioning
confidence: 99%